Investigations of the Expression of Carcinoembryonic Antigen at the Surface of Cultured Human Colon Carcinoma Cells - Rosenthal, Lee Kenneth (My University, 1978)
A number of cellular products present during fetal development, but absent from normal adult tissues, have been shown to be re-expressed in cancer cells. One example of these oncofetal substances is carcinoembryonic antigen (CEA). Studies were undertaken to examine the expression of CEA at the surface of human colon carcinoma cells grown in vitro and to develop a radioimmunoassay for quantitation of CEA and antibodies to CEA in the serum of cancer patients.
Antibodies specific for CEA were prepared in goats and these antibodies were found to induce polar redistribution or capping of the antigen. As with other systems in which polar redistribution of surface molecules have been studied, the capping was temperature-dependent and required an intact microfilament system. Fluorescent-labeled antibodies were utilized to demonstrate that while CEA would undergo capping, blood group antigen A did not, hence these antigens exist as separate molecules at the cell surface. The capping process was further characterized using ¹²⁵I-labeled antibodies and it was demonstrated that upon capping the majority of cell surface CEA underwent endocytosis. The ability to specifically remove CEA from the cell surface with antibody was used to demonstrate a rapid reappearance of CEA on the tumor cell surface, and this reappearance appeared to require protein synthesis.
A precise quantitative radioimmunoassay for CEA was developed and used to determine the amount of CEA expressed on cell surfaces. Various strains of cells were established in vitro which differed in the amount of CEA they produced. Two strains which differed in the amount of CEA expressed at their cell surfaces were shown to be equally tumorigenic in nude mice, which suggested a lack of correlation between CEA production and tumorigenicity.
The radioimmunoassay was also used to study the control of genetic expression of CEA. There was a direct correlation between the amount of cell surface CEA and the amount of CEA secreted into the culture medium. Control over the level of CEA expressed by various strains appeared genetically stable. Yet, a number of lines of evidence suggested that the parental population from which the strains were derived was heterogeneous with respect to CEA synthesis.
The effects of various inducing agents on CEA expression by various cell strains was examined. One strain (HCT-8 Nu2), a very low CEA producing strain, could be induced to express high levels of CEA by inclusion of theophylline in the culture medium. This effect appeared after three days of incubation and reached a maximum after five days. Enhanced expression was dosedependent and time-dependent, requiring continual presence of the drug. The effect also appeared to require continual protein synthesis and did not cause marked alteration of cell morphology or growth. It was demonstrated that the effect was not density-dependent and did not appear to be due to selective proliferation of a high expressor population. Further, the effect could not be mimicked with dibutyryl cyclic adenosine monophosphate. Similarly, another strain (HCT-8R) could be induced to produce higher levels of CEA with bromodeoxyuridine (BrdU). This effect was not as dramatic as the theophylline effect and only appeared transiently. The response to BrdU was dose-dependent.
The specific inhibition of binding of ¹²⁵I-Iabeled anti-CEA antibodies by unlabeled anti-CEA antibodies, was used to demonstrate that no antibodies to CEA could be detected in control or cancer patient sera. The radioimmunoassay was also examined to determine its ability to quantitate the amount of CEA in serum from cancer patients and controls. It was determined that this test could measure comparable ranges of standard reference CEA, obtained from international or marketed sources. The results obtained from tests of patient sera closely correlated with results obtained using a marketed assay kit. A limited number of sera from patients was examined for CEA using the assay. Comparable percentages of patients with CEA-related cancers were found positive by my assay as reported in studies using standard assays. However, my assay appeared to have greater specificity than standard assays in that a lesser percent of patients without CEA-related cancers were positive.
Keywords: Medical Sciences; Medical Sciences